Acute Behavior of Oxygen Consumption, Lactate Concentrations, and Energy Expenditure During Resistance Training: Comparisons Among Three Intensities - Gustavo A. João; Gustavo A. João; Gustavo P. L. Almeida; Lucas D. Tavares; Lucas D. Tavares; Carlos Augusto Kalva-Filho; Nelson Carvas Junior; Francisco L. Pontes; Julien S. Baker; Danilo S. Bocalini; Aylton J. Figueira (Frontiers Media S.A., 2021)
Purpose: This study aimed to compare the oxygen consumption, lactate concentrations, and energy expenditure using three different intensities during the resistance training sessions.Methods: A total of 15 men (22.9 ± 2.61 years) experienced in resistance training underwent 3 sessions composed of 8 exercises (chest press, pec deck, squat, lat pull-down, biceps curl, triceps extension, hamstring curl, and crunch machine), which were applied in the same order. The weight lifted differed among the sessions [high session: 6 sets of 5 repetitions at 90% of 1-repetition maximum (1-RM); intermediary session: 3 sets of 10 repetitions at 75% of 1-RM; and low session: 2 sets of 15 repetitions at 60% of 1-RM]. The oxygen consumption (VO2)-during and after (excess post-exercise oxygen consumption (EPOC)) the session, blood lactate concentration, and energy expenditure (i.e., the sum of aerobic and anaerobic contributions, respectively) were assessed.Results: The VO2 significantly decreased in the function of the weight lifting (F(2.28) = 17.02; p < 0.01; ηG2 = 0.32). However, the aerobic contributions significantly increase in the function of the weight lifting (F(2.28) = 79.18; p < 0.01; ηG2 = 0.75). The anaerobic contributions were not different among the sessions (p > 0.05; ηG2 < 0.01). Thus, the total energy expenditure during the session (kcal) significantly increased in the function of the weight lifting (F(2.28) = 86.68; p < 0.01; ηG2 = 0.75). The energy expenditure expressed in time unit (kcal·min−1) was higher in low session than in high session (F(2.28) = 6.20; p < 0.01; ηG2 = 0.15).Conclusion: The weight lifted during resistance training-induced different physiological responses, which induced higher energy expenditure per unit of time during the low session.